PENGEMBANGAN PRODUK OLAHAN JAMUR TIRAM MENJADI BAKSO DAN NUGGET SEBAGAI PELUANG USAHA DI DESA LEMBUAK KECAMATAN NARMADA - Sanita Sari, Ni Wayan; Savitri, Nila; Satria, Agung; Novianti, Nining; Putri, Inessa Ladiza; Kumala, Audi Zhazha Indra; Aida, Ade Nurul; Hendrawan, Lalu; Suryahadi, Rahman; Zhachary , Muhammad Reyhan (Jurnal Wicara Desa, 2023)
Oyster Mushroom (Pleurotus ostreatus) is one of the edible mushrooms which has potential in the food and health sector. Oyster mushroom has a texture similar to meat with a unique taste and soft taste, making oyster mushroom a popular food ingredient among consumers. In addition, oyster mushrooms are also rich in nutritional content, they contain protein belonging to vegetable protein, carbohydrates, fiber, B vitamins, vitamin D, minerals, and other bioactive compounds. In the world of food, oyster mushrooms can be processed into various preparations such as meatballs and nuggets. In Lembuak Village, most of the people only sell fresh oyster mushrooms without processing them first. The aim of this activity is to develop processed oyster mushrooms into long-lasting frozen food products. The method used in the activity consists of four stages, namely socialization, processing, packaging, and marketing. The development of processed oyster mushrooms deserves to be socialized to the public as a business opportunity. The result of the development of processed oyster mushroom products into meatballs and nuggets is to make participants understand the utilization and processing of oyster mushrooms into various preparations which can be used as business opportunities that can increase people's income, where previously the community only sold oyster mushrooms in fresh form without processing them first . So that with this activity it is hoped that it can improve the family economy in Lembuak Village, Narmada District, West Lombok Regency. In general, this activity can increase participants' knowledge and skills in processing oyster mushrooms into finished products such as meatballs and nuggets.